Zn(TFSI)2-Mediated Ring-Opening Polymerization for Electrolyte Engineering Toward Stable Aqueous Zinc Metal Batteries - Liu, Zhenjie; Xi, Murong; Sheng, Rui; Huang, Yudai; Ding, Juan; Tan, Zhouliang; Li, Jiapei; Zhang, Wenjun; Wang, Yonggang (Nano-Micro Letters, 2025)
Practical Zn metal batteries have been hindered by several challenges, including Zn dendrite growth, undesirable side reactions, and unstable electrode/electrolyte interface. These issues are particularly more serious in low-concentration electrolytes. Herein, we design a Zn salt-mediated electrolyte with in situ ring-opening polymerization of the small molecule organic solvent. The Zn(TFSI)2 salt catalyzes the ring-opening polymerization of (1,3-dioxolane (DOL)), generating oxidation-resistant and non-combustible long-chain polymer (poly(1,3-dioxolane) (pDOL)). The pDOL reduces the active H2O molecules in electrolyte and assists in forming stable organic–inorganic gradient solid electrolyte interphase with rich organic constituents, ZnO and ZnF2. The introduction of pDOL endows the electrolyte with several advantages: excellent Zn dendrite inhibition, improved corrosion resistance, widened electrochemical window (2.6 V), and enhanced low-temperature performance (freezing point = − 34.9 °C). Zn plating/stripping in pDOL-enhanced electrolyte lasts for 4200 cycles at 99.02% Coulomb efficiency and maintains a lifetime of 8200 h. Moreover, Zn metal anodes deliver stable cycling for 2500 h with a high Zn utilization of 60%. A Zn//VO2 pouch cell assembled with lean electrolyte (electrolyte/capacity (E/C = 41 mL (Ah)−1) also demonstrates a capacity retention ratio of 92% after 600 cycles. These results highlight the promising application prospects of practical Zn metal batteries enabled by the Zn(TFSI)2-mediated electrolyte engineering. Highlights: 1 A novel electrolyte enabled by Zn(TFSI)2-mediated ring-opening polymerization strategy for highly reversible aqueous zinc metal batteries was proposed. 2 The novel electrolyte has good antioxidant stability and non-inflammability. 3 The novel electrolyte widens the electrochemical window, improves the low-temperature performance, and inhibits Zn dendrite. The Zn metal anode shows an 8200 h lifespan at 1 mAh cm−2 and a 2500 h lifespan at 60% depth of discharge.